Christian Teacher and Anti-Materialistic Actualization according to the Gospel Matthew 6:19-24 - Yakobus Adi Saingo (Sekolah Tinggi Teologi Baptis Indonesia, 2022)
This study aims to examine the actualization of anti-materialistic according to Matthew 6:19-21, 24 in the Christian teaching profession. Empirically, there are problems related to materialistic behavior among teachers and students in the school environment of SMP N 11 Kupang City, which negatively impacts personality, relationships, and educational institutions. The study explores the origin of this materialistic phenomenon by observing the materialistic character and behavior, especially regarding the factors behind the formation of this behavior. It makes Matthew 6:19-21, 24 the focus of analysis. The research method used is the descriptive qualitative method. The subjects of this study were teachers of Christian Religious Education at SMP N 11 Kupang City. The study results show that this materialistic behavior can only be dammed and eroded through the re-establishment of self-values ?? and the presence of a biblical perspective that underlies daily attitudes and behavior.